Ecolinguistics in a Multilingual Society: A Case Study of Adekunle Ajasin University, Nigeria - Ogunyemi, Kehinde Olufemi; Bada, Abiodun Emmanuel (American International Journal of Social Science Research, 2019)
Language, biology, and culture have been intimately related throughout human history. We cannot dispute the fact that we live in an ecolinguistic world, where human beings relate with at least one language. Language has pioneered many interracial relationships and historical milestones. Language is a necessity for basic communication and cultural diversity in human society. In dealing with linguistic aspect of acculturation in a multilingual society, it is pertinent to trace the ecology of language from an individual point of view. This study examined ecolinguistics in a multilingual society using Adekunle Ajasin University as a case study.The research design adopted was descriptive research of survey type. The sample consists of 180 students drawn randomly from the six faculties in the school. Data was collected through a self-constructed questionnaire(r=0.79) distributed to the students. Data collected was analysed using the descriptive statistics of frequency count and simple percentage for the demographic information of the respondents and analysis of research questions. Findings from the data collected unveil the rate at which Nigeria’s native languages are endangered and derogated by foreign languages. Specifically, it was revealed that language is used as the agent of cultural and bio-diversity. Findings of this study also disclosed that English language is predominantly infused into the linguistic culture of the students of Adekunle Ajasin University Akungba-Akoko as it is used as the students’ instrument and expression of thoughts. Conclusions are made by looking critically into the making of individuals’ bio-cultural diversity. It is then concluded that Nigerian’s native languages are considered informal and have a way of limiting ones thought thereby leading to the robustness of foreign language(s) and endangerment of these native languages. This study recommended and advocated for the enrichment and robustness of Nigerian native languages by making sure that our culture is promoted via these native languages.